Communication Skills of Gynaecological Medical Staff Concerning the Patient - Latifi, Hajrullah; Latifi, Drilon (Journal of Health Sciences and Medical Development, 2023)
Effective communication of medical staff in gynaecology and obstetrics, in relation between the doctor and the patient, is essential and of particular importance. Communication helps patients to have trust in the healthcare services provided by the medical staff and can impact the effectiveness and efficiency of treatment. Medical personnel should be careful and sensitive to the patient's needs, understand their problems, and have good communication and information-sharing skills. An informed patient is more likely to understand the diagnosis and treatment, which can enhance cooperation with the doctor. Quick and successful contact by medical personnel can help reduce patient anxiety and stress, affecting the achievement of treatment goals. In gynaecology and obstetrics, effective communication between the doctor, resulting in effective treatment and care, is crucial for the mother and her fetus. The communication between the doctor and the pregnant woman has a close emotional connection, considering the specific condition of pregnant women.